UPAYA KASASI TERHADAP PUTUSAN BEBAS DALAM PERKARA PIDANA - Alvionita, Pini (Katalogis, 2016)
This Research was to identiy the ratiodecidendi behind the sentence of verdict in appeal against a non-guilty verdict and the implication of a legal appeal against a non-guilty verdict in a criminal case. It was a judicial normative research adopting juridical, historical, conceptual approach and cases. The legal resource were primary ones and secondary ones through bibliographical data collection. The collected data were analyzed descriptively and concluded deductively. Reffering to the results of analysis and discussions, it was concluded that : (1) the ratiodecidendi of an appeal by a general prosecutor was based on philosophy (fairness), juridical (certainty) and sociology (benefit). Among the aforementioned 3 basis, the juridical one was the most prominent, and (2) an appeal by a general prosecutor was not acceptable against all non-guilty verdicts, saved to impure acquittals.